1997
DOI: 10.2118/28450-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Technique for Faster Pulse-Decay Permeability Measurements in Tight Rocks

Abstract: Laboratory pulse-decay measurements using a gas or liquid are effective for determining the permeability of rocks in the range from 0.1 md to 0.01 md. The actual measurement time with this pressuretransient technique is fairly short, but pressure pre-equilibration sometimes requires hours. This paper shows how the total time can be reduced significantly, especially if the sample's pore volume (PV) is measured independently or estimated accurately. Permeability is calculated from "late-time" measurements. Strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
179
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(188 citation statements)
references
References 10 publications
(7 reference statements)
4
179
0
3
Order By: Relevance
“…Routine core analysis was carried out. Since the 213 conventional steady-state method for determining permeability of very low permeability samples (<1 214 mD) is difficult and takes a very long time, selected plug samples were measured using a pulse-decay 215 approach with a 700 psig (4.82 MPa) confining pressure (Jones, 1997). Nuclear magnetic resonance 216 spectroscopy was also carried out on a selection of samples in the laboratory, and it was found that this 217 data was helpful in distinguishing between the petrofacies which we have defined for the Kometan 218 formation.…”
mentioning
confidence: 99%
“…Routine core analysis was carried out. Since the 213 conventional steady-state method for determining permeability of very low permeability samples (<1 214 mD) is difficult and takes a very long time, selected plug samples were measured using a pulse-decay 215 approach with a 700 psig (4.82 MPa) confining pressure (Jones, 1997). Nuclear magnetic resonance 216 spectroscopy was also carried out on a selection of samples in the laboratory, and it was found that this 217 data was helpful in distinguishing between the petrofacies which we have defined for the Kometan 218 formation.…”
mentioning
confidence: 99%
“…In addition to the GRI method, the other widely used laboratory technique to measure source-rock permeability is the pressure pulse-decay method (Jones 1997). Comparisons between source-rock permeability measurements with GRI and pulse-decay methods have been discussed by several groups (Cui et al 2009;Heller et al 2014).…”
Section: Correction Of Laboratory Permeability Measurementsmentioning
confidence: 99%
“…The advantage of this approach is that the test setup and data interpretation procedure are relatively simple. However, it generally takes a relatively long time to equilibrate the test system from one test pressure to the next one (Jones 1997).…”
Section: Introductionmentioning
confidence: 99%
“…For samples with permeability below 0.1 mD, permeability was measured using a pulse-decay technique (Jones, 1997) using a modified Corelabs PDP 200 pulse decay permeameter that has been adapted so that measurements can be made at up to 70 MPa confining pressure. Permeability was calculated using the software for the PDP 200 supplied by Corelabs as in Jones (1997). Samples with a higher permeability were measured using steady state permeametry (API, 1998).…”
Section: Accepted Manuscriptmentioning
confidence: 99%